2017
DOI: 10.5296/jfi.v1i1.12278
|View full text |Cite
|
Sign up to set email alerts
|

Control of Sprouting of Yam (Dioscorea rotundata) and Sweet Potato (Ipomoea batatas) using African Cardamon (Aframomum danielli), Turmeric (Curcuma longa) and Clove (Syzygium aromaticum)

Abstract: This study investigated the effects of the aqueous extracts of Aframomum danielli, Turmeric and Clove in sprouting of yam (Dioscorea rotundata) and sweet potato (Ipomoea batatas). The sliced tubers were dipped into the aqueous extracts of A. danielli, turmeric and Clove, each at concentrations of 5%, 10% and 15%. The tubers were allowed to stand in the solution for 5 and 10 minutes. Distilled water was used in the control samples. The yam slices were air dried after removal from the liquids, placed in paper bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Curcumin has a predominant yellow colour, so the addition of curcumin significantly ( p < 0.05) affected the colour of IRC and resulted in the decrease in the L* value of IFRC [ 18 ]. This result is supported by Adegoke et al [ 17 ], who reported that biscuits formulated with the flour blends containing turmeric powder had lower L* values than did the control, and thus resulted in a darker colour. Furthermore, a positive a* value indicates redness while a negative a* value shows the greenness of a sample, whereas a positive b* value measures yellowness and a negative b* value indicates the blueness of a sample.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Curcumin has a predominant yellow colour, so the addition of curcumin significantly ( p < 0.05) affected the colour of IRC and resulted in the decrease in the L* value of IFRC [ 18 ]. This result is supported by Adegoke et al [ 17 ], who reported that biscuits formulated with the flour blends containing turmeric powder had lower L* values than did the control, and thus resulted in a darker colour. Furthermore, a positive a* value indicates redness while a negative a* value shows the greenness of a sample, whereas a positive b* value measures yellowness and a negative b* value indicates the blueness of a sample.…”
Section: Resultssupporting
confidence: 67%
“…The use of a low cooking temperature in preparing IFRC-S may contribute to the retention of a higher amount of curcumin as compared to that under other methods. The brightness (L* value) decreases as curcumin increases while a* and b* values increase as curcumin increases [17,18]. Values are expressed in mean ± standard deviation (n = 3).…”
Section: Colour Of Irc and Ifrcmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural sources of polysaccharides, such as citrus peels and sea weeds, also hold promising results in encapsulating the curcumin to enhance its bioactivity [ 15 ]. Such formulations can be used to produce products such as mouthwash [ 16 ], supplements [ 17 ], beverages, biscuits [ 18 ], milk [ 19 ], sausage [ 20 ], pasta, cheese [ 19 ], bread, and other daily household foods. It is pertinent to mention that there are some options already on the market in relation to commercial products.…”
Section: Introductionmentioning
confidence: 99%
“…The collision and interference of energy with matter has the possibility of bringing about transformation in the matter provided that the energy is able to have direct contact and collision with the particles of the matter [28]. The use of chemical energy which was successfully used to control sprouting in sweet potatoes (matters) had been reported not to be successful in controlling sprouting in yam tubers [29,30]. This is as a result of chemical energy not having direct contact and collision with the points where the sprouting emerges from the yam tuber.…”
Section: Introductionmentioning
confidence: 99%